Size Exclusion Chromatography: เทคนิคแห่งการวิเคราะห์ น้ำหนักโมเลกุลของพอลิเมอร์: Size Exclusion Chromatography: A technique of molecular weight determination of polymer - Wangtaveesab, Temsiri (Asian Health, Science and Technology Reports, 2011)